The Effect of Exchange Rate Fluctuations on a Trade Balance, the case of Russia. - Masliukova, Tatiana (2015)
This thesis examines the impact of exchange rate fluctuation on trade balance. In order to examine the effect of depreciation of domestic currency on the trade balance, the data for Russian Federation was used. The time series analysis includes quarterly data since 2000 till 2014. With help of cointegration model it was concluded that there is a long-term dependence between exchange rate and trade balance. Regression results suggest that the impact of depreciation of national currency on trade balance of Russia is positive after one quarter, while response of exchange rate depreciation without time lag is deterioration of the balance of trade. This empirical evidence supports the pattern of movement described by the J-Curve.